Planar Functionalized Surfaces for Direct Immunoaffinity Desorption/Ionization Mass Spectrometry - Pompach, Petr; Nováková, Jana; Kavan, Daniel; Benada, Oldřich; Růžička, Viktor; Volný, Michael; Novák, Petr (Clinical chemistry, 2016)
BACKGROUND: Recent studies show that the haptoglobin phenotype in individuals with diabetes mellitus is an important factor for predicting the risk of myocardial infarction, cardiovascular death, and stroke. Current methods for haptoglobin phenotyping include PCR and gel electrophoresis. A need exists for a reliable method for high-throughput clinical applications. Mass spectrometry (MS) can in principle provide fast phenotyping because haptoglobin α 1 and α 2, which define the phenotype, have different molecular masses. Because of the complexity of the serum matrix, an efficient and fast enrichment technique is necessary for an MS-based assay. METHODS: MALDI plates were functionalized by ambient ion landing of electrosprayed antihaptoglobin antibody. The array was deposited on standard indium tin oxide slides. Fast immunoaffinity enrichment was performed in situ on the plate, which was further analyzed by MALDI-TOF MS. The haptoglobin phenotype was determined from the spectra by embedded software script. RESULTS: The MALDI mass spectra showed ion signals of haptoglobin α subunits at m/z 9192 and at m/z 15 945. A cohort of 116 sera was analyzed and the reliability of the method was confirmed by analyzing the identical samples by Western blot. One hundred percent overlap of results between the direct immunoaffinity desorption/ionization MS and Western Blot analysis was found. CONCLUSIONS: MALDI plates modified by antihaptoglobin antibody using ambient ion landing achieve low nonspecific interactions and efficient MALDI ionization and are usable for quick haptoglobin phenotyping.
Keywords: Surface Properties; Software; Phenotype; protilátky; Humans; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Chromatography, Affinity; Antibodies; Blotting, Western; lidé; fenotyp; spektrometrie hmotnostní - ionizace laserem za účasti matrice; chromatografie afinitní; software; haptoglobiny; povrchové vlastnosti; western blotting; Haptoglobins